2017
DOI: 10.1245/s10434-017-5968-2
|View full text |Cite
|
Sign up to set email alerts
|

Margin Proximity Correlates with Local Recurrence After Mastectomy for Patients Not Receiving Adjuvant Radiotherapy

Abstract: For patients undergoing mastectomy for breast cancer, a wider final margin correlated with a reduced risk for LR. The rates for LR were similar between SSM/NSM and SM despite higher rates of intraoperative reexcision for SSM/NSM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…The locoregional recurrence of this population was 3.0%, with a median follow‐up time of 39 (IQR: 21–59) months. This is in accordance with results reported for sparing mastectomies in the literature 17,21,26–29 . Agha et al 30 reported on a metanalysis of SSMs and NSMs a local recurrence rate of 3.3% and 3.9%, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The locoregional recurrence of this population was 3.0%, with a median follow‐up time of 39 (IQR: 21–59) months. This is in accordance with results reported for sparing mastectomies in the literature 17,21,26–29 . Agha et al 30 reported on a metanalysis of SSMs and NSMs a local recurrence rate of 3.3% and 3.9%, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Some studies in the literature associate close tumor margins with locoregional recurrence, namely in breast cancer surgery 29,38 . In our analysis, the close margin was not a locoregional recurrence risk factor ( p = 0.69).…”
Section: Discussionmentioning
confidence: 43%
“…During the discussion, it became obvious that there are wide international variations in clinical practice concerning positive or close margins after NSM, ranging from further surgery to post-mastectomy radiotherapy to no treatment. A large patient series at Mayo Clinic showed that the overall 5-year risk of local recurrence was higher in patients with a margin ≤ 2 mm compared to a margin > 2 mm (11.2% vs. 3.1%), with the proximity of the final margin being an independent significant risk factor for local recurrence [ 45 ]. However, in a retrospective single-center study of 64 SSM procedures with a positive mastectomy margin towards the skin in the area of the primary tumor, only 13 (20%) had residual cancer in simultaneous re-excisions of the subcutaneous tissue, suggesting a high incidence of false-positive margins [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…4 studies additionally reported hazard ratios for distant disease-free recurrence. The association between margin status and LR was reported in 7 studies (4,15,20,28,36,39,44). In the univariable analyses, positive or close margins were associated with increased LR (HR 2•88 (95% CI 2•06,4•03)) (Supplementary Figure 1).…”
Section: Reporting Standards and Methodological Qualitymentioning
confidence: 88%